Analisis Ketidakhadiran Partua Ibale Mengikuti Ibadah Minggu di GKPPD Desa Simbruna, Kecamatan Siempat Rube, Kabupaten Pakpak Bharat (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the factors influencing the absence of partua ibale (male congregants who are heads of households) in attending Sunday services at GKPPD Simbruna Village, Siempat Rube District, Pakpak Bharat Regency. The research employed a qualitative method, with data collected through observation, in-depth interviews, and documentation involving several congregants, church leaders, and community members. The findings reveal that absenteeism among partua ibale is influenced by both internal and external factors. Internal factors include a lack of spiritual motivation, boredom due to lengthy and less engaging sermons, low awareness of gratitude to God, and weak personal commitment to church participation. External factors include the long distance to the church, heavy family responsibilities, economic challenges, and the absence of exemplary conduct from church elders. The study concludes that the attendance of partua ibale in Sunday services is not solely a personal matter but also reflects the church’s effectiveness in providing pastoral care, strengthening fellowship, and encouraging active male participation in worship.